Oxidant and antioxidant status in the hypo- hyperthyroid patients before and after treatment - Gur, Biray; Halifeoglu, Ihsan; Aydin, Suleyman (Amer Soc Biochemistry Molecular Biology Inc, 2004)
[Abstract Not Available]